Accounting for unobservable preference heterogeneity and evaluating alternative anchoring approaches to estimate country-specific EQ-5D-Y value sets: a case study using Spanish preference data - Ramos-Goñi, JM; Oppe, M; Estévez-Carrillo, A; Rivero-Arias, O (Elsevier, 2021)
Objectives: The EuroQol Group published the EQ-5D-Y valuation protocol. This protocol suggested the use of two valuation techniques to elicit preferences: Composite Time-Trade-Off (C-TTO) and Discrete Choice Experiments (DCE). The protocol left the decision of what modelling approach to use open for researchers. Our aims were to explore modelling strategies allowing generation of EQ-5D-Y value sets and to produce an EQ-5D-Y Spanish value set.